NEW ACROPOMATIFORM FOSSILS FROM THE UPPER KUEICHULIN FORMATION (LOWER PLIOCENE), NORTHERN TAIWAN (Rivista italiana di Paleontologia e Stratigrafia, 2024)
The Indo-West Pacific is home to a diverse array of modern fish species, and the study of their fossils can provide valuable insights into the origins and evolution of this biodiversity. This report presents rare remains of five individuals of acropomatiform fish, including a semi-articulated skeleton, recovered from the Upper Kueichulin Formation (Lower Pliocene) in northern Taiwan. The fossils are preserved in the form of nodules discovered at the locality known for abundant marine crustaceans and echinoderms. These specimens can be assigned to the family Stereolepididae, based on morphology of the opercle with the presence of two spines, a preopercle characterized by serrations on the posterior margin and denticulations on the ventral margin, and a distinctive skull architecture. Differences in skull morphology distinguish these specimens from other species within the genus and thus are described as Stereolepis arcanum n. sp. Significantly, the species represents the oldest known record of the family globally and stands as the second known fossil representative. This discovery not only enhances our understanding of the palaeobiodiversity of fish fauna in the Indo-West Pacific during the Neogene, but also highlights the importance of further research efforts in this area.